A certain sequence of functions involving the Aleph function - Agarwal P.; Chand M.; Onur Kiymaz İ.; Çetinkaya A. (Open Physics, 2016)
Sequences of functions play an important role in approximation theory. In this paper, we aim to establish a (presumably new) sequence of functions involving the Aleph function by using operational techniques. Some generating relations and finite summation formulas of the sequence presented here are also considered.